ANALISIS PENERIMAAN PAJAK HIBURAN, PAJAK HOTEL, PAJAK RESTORAN DAN PERTUMBUHAN EKONOMI DI PROVINSI KEPULAUAN BANGKA BELITUNG - Veti Verawati; Dedi Susanto (LPPM STIE PERTIBA Pangkalpinang, 2018)
This research is intended to describe Visit Bangka Belitung Archipelago Program, and also the entertainment tax, hotel tax, restaurant tax revenue and economic growth in Kepulauan Bangka Belitung Province before and after that program. The object of this research is Kepulauan Bangka Belitung Province years 2005 – 2014. Visit Bangka Belitung 2010 is one of Bangka Belitung Culture and Tourism Office program that aims to develop the tourism sector and also other economic sectors. The research method used is descriptive causality method with the event study approach. The data used document method. The hypothesis testing by using t-test (average of two related population test). The amount of entertainment tax, hotel tax, restaurant tax revenue and economic growth in Kepulauan Bangka Belitung Province is increasing year by year. And based on the statistical test, the result showed that Visit Bangka Belitung Archipelago has a positive impact on entertainment tax, hotel tax, restaurant tax revenue and economic growth in Kepulauan Bangka Belitung Province. It means the holding of the program also increase the amount of entertainment tax, hotel tax, restaurant tax revenue, and economic growth.